Differentiated Learning Management : A Theoritical Integration of Tomlison’s Model within The Merdeka Curriculum Framework - Pualam Ariarta, Aliffany; Zahroh, Fatimatuz; Hadi, Rizal (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Merdeka Curriculum is an alternative educational approach that focuses more on skill development and self-empowerment. In its implementation, a learning concept called differentiated learning is designed. This research aims to find out 1) The concept of differentiated learning management; 2) The principles applied; and 3) The role of teachers in differentiated learning management. Using qualitative research method with literature study research type. Data sources are obtained through literature in the form of scientific research journals, proceeding articles, books or some other forms of documents collected from Google Scholar, Sinta Kemendikbud, university libraries, Google Books, and some other digital sources. The data analysis technique uses thematic analysis, which is an analytical technique that allows researchers to identify and categorize thematic patterns from the previously collected literature. The results of this study reveal 1) The stages of differentiated learning management: the planning stage begins with a diagnostic assessment to diagnose students' readiness and learning styles, at the organizing stage the teacher determines the media that is suitable for students' learning styles so that the implementation stage can run optimally, then the stage of controlling learning outcomes through formative assessment. 2)The principles that need to be considered are learning environment, quality curriculum, continuous assessment, responsive learning and leadership and classroom routines. 3)In this learning, the role of teachers, especially their creativity in management, is needed to create effective and efficient learning. The existence of this research is a reference for educators to be able to carry out learning in the independent curriculum effectively and efficiently, one of which is by implementing differentiated learning